West Bank and Gaza : Palestinian Trade, West Bank Routes - World Bank (Washington, DC, 2012)
The World Bank analyzed the logistics of trade corridors from Gaza through Egypt as an alternative to sending exports via Israel. This paper extends this work and examines the viability of different trade routes from the West Bank. Another earlier paper describes the complex agglomeration of physical obstacles, administrative barriers and permit policies that Israel uses to restrict movement in the West Bank. This paper also builds on this work by quantifying some of the resulting costs. West Bank enterprises have essentially two options to access the world market: (a) out through Israeli ports or airport; and (b) across the Jordan River and out through Jordan ports or airport. While, it is also possible to send goods across Israel and through Egypt, this route is currently uneconomical.